Mixing School Business with Pleasure: Prevalence of Substance Abuse among Secondary School Students in Lagos State of Nigeria - Onigbogi, Olanrewaju; Ojo, Omobola; Babalola, Oluwatoyin (European Scientific Journal, ESJ, 2023)
Background: Substance abuse among in-school youth has been found to be on the increase all over the world. This behavior is usually accompanied by physical and mental health consequences which are of public health significance. This study aimed at determining the prevalence of use of illicit drugs among senior secondary school students in Lagos State of Nigeria. Method: This was a descriptive cross-sectional study among 422 senior secondary school students selected by multistage sampling technique. Data were collected using a pre-tested structured, self-administered questionnaire and was analysed using Statistical Package for Social Science (SPSS) version 21. The statistical analyses of frequency counts, percentages and chi square were set at a level of significance of p â‰¤0.05. The Chi-square and Fisher's exact tests were used to determine the association between categorical variables. Results: A total of 422 students participated in this study with mean age of 16.30 Â± 1.72 years. Out of which 205 (48.6%) were males and 217 (51.4%) were females. About 68% of respondents understood the meaning of illicit drugs. The overall knowledge of students on illicit drugs was good (66.9%), so also for positive attitude (61.6%). There was however a statistically significant association between the knowledge of the respondents and their attitude towards illicit drugs. The awareness of substance abuse was high 89.6% and sources of information were mostly from the television. The most commonly used drugs reported were opiates, codeine contained in cough syrups and tramadol (11.6%), followed by tranquillizers sedative hypnotic (9%), Hallucinogen (5.6%) and Amphetamines (5.3%) with the influencers mainly the parents and family friends. Conclusion: The study reveals that despite overall good knowledge and positive attitude towards substance abuse, some students were still engaged in the practice. There is a need to start the teachings from homes, enforce disciplinary actions against culprits by the policy makers and effect educational programs about substance abuse in schools and social media.